Isolated angiokeratomas of the tongue: A rare entity - Rizwan Hamid; Altaf H Chalkoo; Inderpreet Singh; Suhail Wani; Sheikh Bilal (Wolters Kluwer Medknow Publications, 2019)
Angiokeratomas consist of ectasias of dermal capillaries associated with an acanthotic and hyperkeratotic overlying epidermis. These dark red-to-purple, papular vascular anomalies can vary considerably in size, depth, and location. It is a skin disorder that rarely involves oral cavity. It can occur in localized or generalized form and is often associated with underlying metabolic disorder such as Fabry's disease and fucosidosis. It has many clinical variants with the same underlying histopathology. Mucosal involvement, including the oral cavity, is occasionally found either as a component of the systemic variety, called angiokeratoma corporis diffusum, or associated with cutaneous lesions in more locations. Isolated oral involvement seems to be rather infrequent, and only eighteen cases have been described in the world literature thus far. Isolated multiple angiokeratomas of tongue without plaque formation have been reported only four times before this. Here, we report a fifth case of isolated multiple angiokeratomas of tongue in a 16-year-old female which was confirmed by immunohistochemical pattern in consonance with a blood vessel origin, with expression of CD31, CD34, and von Willebrand factor. The lesion did not express D2-40 and CD45. No other malformation or metabolic disorder was found in the patient.